PENGARUH PELATIHAN PASAR MODAL TERHADAP MINAT BERINVESTASI - Arniati Arniati (Universitas Muhammadiyah Gresik, 2022)
The purpose of the study was to determine the effect of capital market training on investment interest. The research was carried out at the Faculty of Economics and Business, University of Muhammadiyah Makassar on Undergraduate Development Economics students using multiple linear regression analysis techniques. In determining the research sample using the Slovin formula from a known population. From the calculation results, a sample of 75 active student respondents from the class of 2019 was obtained and took introductory capital market courses. The type of data used in the study is qualitative data which is quantified in the form of the results of respondents' answers which have been stated in the form of numbers by a questionnaire which is measured using a Likert scale. The results showed that capital market training had a positive effect on investment interest.